ANESTEZJOLOGIA I INTENSYWNA TERAPIAParavertebral block for thoracotomy. Dosage of local anaesthetics - Szebla, Renata; Machała, Waldemar; Szebla, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduce : Thoracic paravertebral analgesia has been described as an effective and safe method of regional analgesia for thoracotomy. The aim of the study was to compare TPVA (thoracic paravertebral analgesia) with 15 ml of 0.5% bupivacaine and 30 ml 0.25% bupivacaine, for pain control and haemodynamics, after thoracotomy Material and Methods : Sixty ASA 1 and 2 adult patients were randomly assigned to two equal groups and received either: (TPVA15) 15 ml 0.5% bupivacaine, or (TPVA30) 30 ml 0.25% bupivacaine injected into the paravertebral space before the thoracotomy. General anaesthesia was conducted in both groups. All patients received 0.25% bupivacaine: 15 ml after the surgery and continuous infusion of 0.1 ml/kg/h during the postoperative period. Results : The average blood pressure, the heart rate and fentanyl dose administered intraoperatively in both groups were similar. Pain control and subjective evaluation of anaesthesia were better in the TPVA30 group. Conclusions : 1. The effect of paravertebral analgesia on blood pressure and heart rate is minimal. 2. Thoracic paravertebral anaesthesia is an effective method to control post-thoracotomy pain. The pain relief is better if the volume of local anaesthetic solution is 30 ml.